Remediation of heavy metal contaminated soils: Phytoremediation as a potentially promising clean-up technology - Marques, Ana P. G. C. (2010)
Increased soil pollution with heavy metals due to various human and natural activities has led to a growing need to address environmental contamination. Some remediation technologies have been developed to treat contaminated soil, but a biology-based technology, phytoremediation, is emerging. Phytoremediation includes phytovolatilization, phytostabilization, and phytoextraction using hyperaccumulator species or a chelate-enhancement strategy. To enhance phytoremediation as a viable strategy, microbiota from the rhizosphere can play an important role, but the use of genetic engineering can also increase the success of the technique. Here we review the key information on phytoremediation, addressing both potential and limitations, resulting from the research established on this topic.